2022
DOI: 10.1021/acs.inorgchem.2c01867
|View full text |Cite
|
Sign up to set email alerts
|

Function of Internal and External Fe in a Ni-Based Precatalyst System Toward Oxygen Evolution Reaction

Abstract: It is well known that the “iron” impurity will influence the oxygen evolution reaction (OER) in an alkaline electrolyte, especially for the Ni-based electrocatalyst. Many research studies have investigated the function of Fe in the OER active phase, such as M(OH)2/MOOH (M = Ni and/or Fe), while, surprisingly, very few studies have examined the function of Fe in the “precatalyst” system. Accordingly, in this work, the Ni3–x Fe x P (x = 0, 0.5, 1) series as an Ni-based precatalyst was employed to inspect the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Many studies have indeed shown that Fedoped nickel oxides are promising electrocatalysts for the OER. [70][71][72][73][74] Similar to Fe-doped nickel oxides, the effect of Fedoping in Li-layered metal oxides as electrocatalysts for the OER has been investigated. A series of Co-based oxides, LiCo 1-x M x O 2 (M = Ni, Fe and Mn) was also investigated by Lu et al using the same preparation methods as for LiCoO 2 and Li 0.5 CoO 2 .…”
Section: Li-layered Co-based Alloy Oxidesmentioning
confidence: 99%
“…Many studies have indeed shown that Fedoped nickel oxides are promising electrocatalysts for the OER. [70][71][72][73][74] Similar to Fe-doped nickel oxides, the effect of Fedoping in Li-layered metal oxides as electrocatalysts for the OER has been investigated. A series of Co-based oxides, LiCo 1-x M x O 2 (M = Ni, Fe and Mn) was also investigated by Lu et al using the same preparation methods as for LiCoO 2 and Li 0.5 CoO 2 .…”
Section: Li-layered Co-based Alloy Oxidesmentioning
confidence: 99%
“…where A geo is the geometric area of the glassy carbon electrode, which equals 0.19625 cm 2 . The specific current density per ECSA (j s ) was calculated as shown in eq 3:…”
Section: T H Imentioning
confidence: 99%
“…Water electrolysis has been regarded as one of the most promising strategies for widespread hydrogen production. PEMWEs and alkaline water electrolyzers (AWEs) represent two major hydrogen production technologies. PEMWEs can produce much purer hydrogen at a larger current density and a higher energy efficiency as compared to AWEs. However, a grand challenge of PEMWEs is the slow kinetics of acidic OER, which involves multiple electron transfer and a high reaction energy barrier .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Therefore, it is imperative to use more affordable and abundant non-noble metal compounds as catalysts for the electrocatalytic OER. In this regard, earth-abundant metals (Ni, Co, Fe, and Cu) [12][13][14][15] and their associated suldes, [16][17][18][19] oxides, [20][21][22] phosphides, [23][24][25] selenides, [26][27][28] and nitrides [29][30][31] are being aggressively investigated as electrocatalysts for the OER. Out of these, transition-metal nitrides exhibit exceptional OER performances due to their distinct electronic structure and unique physical and chemical characteristics.…”
Section: Introductionmentioning
confidence: 99%